Thermodynamic properties of non-Hermitian Nambu-Jona-Lasinio models - Felski, Alexander; Beygi, Alireza; Klevansky, Sandra Pamela (Physical review, 2023)
We investigate the impact of non-Hermiticity on the thermodynamic properties of interacting fermions by examining bilinear extensions to the 3+1-dimensional SU(2)-symmetric Nambu-Jona-Lasinio (NJL) model of quantum chromodynamics at finite temperature and chemical potential. The system is modified through the anti-PT-symmetric pseudoscalar bilinear ¯ψγ5ψ and the PT-symmetric pseudovector bilinear iBν¯ψγ5γνψ, introduced with a coupling g. Beyond the possibility of dynamical fermion mass generation at finite temperature and chemical potential, our findings establish model-dependent changes in the position of the chiral phase transition and the critical end point. These are tunable with respect to g in the former case, and both g and |B|/B0 in the latter case, for both lightlike and spacelike fields. Moreover, the behavior of the quark number, entropy, pressure, and energy densities signal a potential fermion or antifermion excess compared to the standard NJL model, due to the pseudoscalar and pseudovector extension, respectively. In both cases, regions with negative interaction measure I=ε−3p are found. Future indications of such behaviors in strongly interacting fermion systems, for example, in the context of neutron star physics, may point toward the presence of non-Hermitian contributions. These trends provide a first indication of curious potential mechanisms for producing non-Hermitian baryon asymmetry. In addition, the formalism described in this study is expected to apply more generally to other Hamiltonians with four-fermion interactions, and thus, the effects of the non-Hermitian bilinears are likely to be generic.
Gesehen am 19.04.2023